Patients' self-reported medical care for low back pain: a nationwide population-based study. Issue 9 (5th September 2022) - Gomes, Luís Antunes; Cruz, Eduardo Brazete; Henriques, Ana Rita; Branco, Jaime C; Canhão, Helena; Rodrigues, Ana Maria
Abstract : Objectives: To estimate the prevalence of medical care-seeking among adults with low back pain (LBP) and to characterise and compare use of diagnostic procedures and medical management between primary and secondary care. Design: Cross-sectional study. Setting: Data from the EpiReumaPt, a nationwide population-based study conducted in Portugal including a representative sample of non-institutionalised adults (n=10 661) stratified by administrative territorial units was analysed. Participants: Individuals who self-reported history of LBP within the previous 12 months (n=6434) and sought medical care for this problem in the same period (n=2618). Outcome measures: Patients' self-reported diagnostic workup and management procedures performed by medical care for LBP collected through a structured questionnaire. Medical care procedures were stratified by level of care. Results: The prevalence of medical care-seeking for LBP was 38.0% (95% CI 35.9% to 40.1%). Primary care in isolation (45.3%) was the most sought level of care. Emergency departments (25.9%) and orthopaedics (19.4%) were the most sought secondary medical specialties. Several pathoanatomical diagnoses were used, supported by laboratory or imaging tests (91.1%). Disc herniation (20.4%) and osteoarthritis (19.7%) were the most frequent diagnoses, and X-ray (63.7%) was the most frequent diagnostic procedure self-reported by individuals. Most (75.1%) reported being treated for LBP: 80.4% with oral medication and 49.9% with injectables. The mean duration of pharmacological treatment was 104.24 (SD, 266.80) days. The use of pathoanatomical diagnoses, laboratory or imaging tests, and pharmacological treatments were generally more frequent for secondary care (p<0.05). Approximately one-quarter of individuals (24.5%) reported seeking care from additional healthcare providers, physiotherapists (66.9%) were the most frequent. Conclusions: Medical care for LBP is frequent and associated with high levels of pathoanatomical diagnoses, imaging and laboratory tests and pharmacological therapy in both primary and secondary care settings. Funding and delivery actions should be prioritised to assure appropriate care for LBP.